(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
In the vast variety of different products today demand adequate sources of inspiration for designers every day has become increasingly challenging. Very recently become fashionable all new products carry the label „eco“ or „bio“, but whether this is just a way to attract consumers’ attention to them, or rather – is building a new behaviour, oriented towards the establishment of responsibility to the planet and its precious resources – that’s the issue, seeking the answer to the author. Looking at the recent past, and tracking the development of different labels until today concludes that the name „green“ or „organic“ must not be used for its own sake, that no longer have a product to be produced only by the fact that economy has a need for it – rather in its design to be rationalized each country, the author adds a new - namely – to consider the so-called. „Second life“ of the product, and how important is the current life cycle of products „from cradle to grave“ to be replaced by a new – „cradle to cradle.“ This should become the responsibility of many people, including designers.